2013
DOI: 10.1063/1.4804338
|View full text |Cite
|
Sign up to set email alerts
|

Reconnection at three dimensional magnetic null points: Effect of current sheet asymmetry

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…Because the reconnection jets impacted the islands obliquely rather than directly, the islands developed net vorticity. In addition to asymmetric inflow reconnection, several groups have investigated asymmetric outflow reconnection (e.g., Oka et al 2008;Murphy et al 2010;Murphy 2010) and reconnection with three-dimensional asymmetry (e.g., Al-Hachami & Pontin 2010;Wyper & Jain 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Because the reconnection jets impacted the islands obliquely rather than directly, the islands developed net vorticity. In addition to asymmetric inflow reconnection, several groups have investigated asymmetric outflow reconnection (e.g., Oka et al 2008;Murphy et al 2010;Murphy 2010) and reconnection with three-dimensional asymmetry (e.g., Al-Hachami & Pontin 2010;Wyper & Jain 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This partially results from sampling the reconnection rate in the jets at high cadence (D = t 2.5) only around the peak times of each jet, due to the impracticality of analyzing all of the data for the entire time series. In addition, fragmented 3D reconnection is the cumulative effect of many reconnection regions (Wyper & Jain 2013;Wyper & Hesse 2015), which smooths out the effect of a single burst of reconnection in the volume. Even so, the high-cadence sampling of the reconnection rate around the peaks also shows some intermittency, particularly for = L N 1.46.…”
Section: Macroscopic Evolutionmentioning
confidence: 99%
“…The rate of reconnection can then be defined as the flux transfer across these surfaces 16 , or past separators which sit at the intersection of different separatrix surfaces 17 . If the non-ideal regions spanning the separatrix surfaces are fragmented then considering flux transfer across segments of a separatrix surface 18,19 or along multiple separators 20 if they exist allows the reconnection rate to be quantified. Unlike 2D, where X-points other than the dominant X-point do not directly contribute to the reconnection rate (although they may indirectly affect it), in 3D reconnection across a separatrix surface in multiple places or at multiple separators all contribute towards the total rate of flux transfer between the main topological domains.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the lack separatrix surfaces against which reconnection can be defined requires a more general approach to the problem. The theory of General Magnetic Reconnection (GMR) encompasses reconnection across separatrices 18,21 as well as describing reconnection in situations without them. The theory of GMR has shown that for a single isolated non-ideal region the rate of reconnection is given by the maximum of E dl on all field lines threading the nonideal region [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%